PENGARUH BOARD GAME EDUKASI POPOHIDATKU TERHADAP PENGETAHUAN PHBS PADA ANAK SEKOLAH MENENGAH PERTAMA USIA 13 TAHUN DI KOTA BENGKULU - Puja Tri Kartika; Hermansyah Hermansyah; Sahran Sahran (JURNAL PENELITIAN TERAPAN KESEHATAN, 2021)
: One of the efforts is towards healthy behavior through a program known as the Clean and Healthy Behavior Program (PHBS) which is carried out systematically and coordinated. The Effects of Play for Increasing Children's Knowledge Games can increase affiliation with peers, reduce pressure, improve cognitive development and can reduce potentially dangerous behaviors. This study aims to determine the effect of education on PHBS knowledge in junior high school students and students in the city of Bengkulu. The design used was a quasi experiment using a pre-post test design with control group design. the subject group was observed before the intervention, then observed again after the intervention. The sample was taken using simple random sampling with 30 people in one group and the entire study sample was 60 people. The research instrument used was a questionnaire made by Titi Sari Banun. Analysis used the Wilcoxon test to compare anxiety variables in groups, while the Mann Whitney-U test was used to compare anxiety variables in both groups. The results of the statistical test show p = 0.009 <α 0.05. so that it can be concluded that there is a difference in average PHBS knowledge before and after being given the educational game board POPOHIDATKU and it can be concluded that there is an influence of the educational board game POPOHIDATKU on Knowledge of PHBS in middle school children aged 13 years in Bengkulu City.